KAMUS ISTILAH ILMU KOMPUTER DENGAN ALGORITMA BOYER MOORE BERBASIS WEB - Dwipa Handayani; Abrar Hiswara (Jurnal Informatika, 2019)
A dictionary is a reference book that contains words and phrases that are usually arranged in alphabetical order along with an explanation of their meaning, usage and translation and function to help recognize new terms. The field of computer science certainly has specific terms related to computers, so it is needed a dictionary of computer terms, currently the existing dictionary is still conventional in its use ineffective and inefficient. The design and manufacture of applications using algorithms by performing a sequence of logical steps in solving problems that are arranged systematically. Algorithms for searching are now growing day by day. Boyer Moore algorithm is one of the search algorithms that is considered to have the best results, namely the algorithm that moves matching strings from right to left. With this web-based dictionary the user is expected to be able to get information quickly, without any limitations on space and time. Keywords: Boyer Moore's Algorithm, Computer Science, Glossary of Terms, Web.